1992
DOI: 10.1016/0014-5793(92)81146-d
|View full text |Cite
|
Sign up to set email alerts
|

Human interleukin‐1 receptor antagonist is expressed in liver

Abstract: Using PCR and Northern blot analysis, an IL‐1 receptor antagonist specific transcript was amplified from HepG2‐ and liver mRNA, cDNA clones coding for IL‐1 receptor antagonist were isolated from a liver cDNA library and sequence comparison revealed complete identity with the secreted, monocytic form of IL‐1 receptor antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Our data establish that only sIL-1Ra, and not icIL-1Ra, is transcribed in hepatic cells, consistent with the results of earlier studies (37). We also observed, however, the presence of a lower molecular form of IL-1Ra in HepG2 cell lysates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data establish that only sIL-1Ra, and not icIL-1Ra, is transcribed in hepatic cells, consistent with the results of earlier studies (37). We also observed, however, the presence of a lower molecular form of IL-1Ra in HepG2 cell lysates.…”
Section: Discussionsupporting
confidence: 93%
“…The IL-1Ra mRNA has been described in HepG2 cells, and IL-1Ra production by hepatocytes was observed during bacteria-induced hepatitis in mice (37,38). The regulation of IL-1Ra production by IL-1 and IL-6 in human primary hepatocytes and HepG2 cells described herein, however, clearly classifies IL-1Ra as an APP.…”
Section: Discussionmentioning
confidence: 61%
“…1C). Previous reports have indicated that hepatocytes express a soluble, secreted form of IL1RN, whereas expression of an intracellular form is negligible (26,32). Therefore, the detected band appears to represent soluble IL1RN.…”
Section: Identification Of Pgc-1␣-regulated Hepatic Inflammatorymentioning
confidence: 91%
“…62 IL-1Ra is expressed in the liver and in hepatoma cells, suggesting a role in regulating IL-1 activity in the liver. 63 In summary, IL-1Ra attenuates the acute phase response both in vivo and in vitro, although species differences may exist.…”
Section: Soluble Cytokine Receptors and Receptor Antagonistsmentioning
confidence: 99%